Effectiveness of antibacterial prophylaxis during induction chemotherapy in children with acute lymphoblastic leukemia. Issue 5 (10th January 2018) - Sulis, M.L.; Blonquist, T.M.; Stevenson, K.E.; Hunt, S.K.; Kay‐Green, S.; Athale, U.H.; Clavell, L.A.; Cole, P.D.; Kelly, K.M.; Laverdiere, C.; Leclerc, J.M.; Michon, B.; et al.
Abstract: Background: Pediatric patients receiving induction chemotherapy for newly diagnosed acute lymphoblastic leukemia (ALL) are at high risk of developing life‐threatening infections. We investigated whether uniform antibacterial guidelines, including mandatory antibacterial prophylaxis in afebrile patients during induction, decreases the incidence of microbiologically documented bacteremia. Methods: Between 2012 and 2015, 230 patients with newly diagnosed ALL (aged 1–21) were enrolled on Dana‐Farber Cancer Institute ALL Consortium Protocol 11‐001 (DFCI 11‐001). Induction therapy, regardless of risk group, included vincristine, prednisone, doxorubicin, methotrexate, and PEG‐asparaginase. Afebrile patients received fluoroquinolone prophylaxis at the initiation of induction and those presenting with fever received broad‐spectrum antibiotics; antibiotics were continued until blood count recovery. Rates of documented bacteremias and fungal infections on DFCI 11‐001 were compared to those on the predecessor protocol (DFCI 05‐001), which included the same induction phase without antibiotic prophylaxis guidelines. Results: Sixty‐six (28.7%) patients received fluoroquinolone prophylaxis, the remaining patients received broad‐spectrum antibiotics. Twenty‐four (36.4%) patients on prophylaxis developed fever and seven (10.6%) developed bacteremia. The overall rate of infection during induction on DFCI 11‐001 was lower than on DFCl 05‐001 (14.3% vs. 26.3%, P < 0.0001) due to a decreased rate of bacteremia (10.9% vs. 24.4%, P < 0.0001). The rate of fungal infections (4.8% vs. 3.6%) and induction death (0.9% vs. 2%) was not significantly different. Conclusion: For children with newly diagnosed ALL, uniform antibiotic administration until blood count recovery, including fluoroquinolone prophylaxis for afebrile patients, reduced the incidence of bacteremia during the induction phase. Larger, randomized studies should be performed to confirm these findings.